Necrotizing fasciitis caused by Aeromonas caviae - Kumar, Simit (Medknow Publications & Media Pvt Ltd, 2012)
Aeromonads are rarely associated with human intestinal and extra-intestinal diseases and syndromes, ranging from relatively mild illnesses such as acute gastroenteritis to life-threatening conditions, including septicemia, necrotizing fasciitis, and myonecrosis. Among the aeromonas species known to cause human infection, Aeromonas caviae has been associated with septicemia and only one reported case of human soft tissue infection. Most of the infections due to aeromonas occur in immunocompromised patients. Herein we describe a successfully treated case of post-traumatic skin and soft-tissue infections due to A. caviae in an otherwise immunocompetent individual.